2015
DOI: 10.3109/19401736.2015.1033697
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Lithobates sylvaticus (Anura: Ranidae)

Abstract: The complete mitochondrial genome of Lithobates sylvaticus (Anura: Ranidae) was sequenced. The genome is a circular molecule of 17,343 bp in length and contains 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and a large non-coding region. The gene order and mitochondrial genome information of L. sylvaticus is similar to most other frogs. The overall AT content of L. sylvaticus mitochondrial DNA is 59.3%. In BI and MLtrees, we found L. sylvaticus is a sister clade to L. catesbeianus. The monophyly of Lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…Gene order, lengths and codon compositions are shown in Table 1. The overall base composition of the heavy strand is 27.7% for A, 28.3% for T, 14.9% for G and 29.1% for C, with an A þ T bias of 59.9%, similar to other ranid species (Hofman et al 2014, Li et al 2014a, 2014b, Ni et al 2015. The genome shows a similar gene organization as other ranids (Kurabayashi et al 2010;Xia et al 2014), but it is the only anuran known so far lacking the tRNA Phe .…”
mentioning
confidence: 77%
“…Gene order, lengths and codon compositions are shown in Table 1. The overall base composition of the heavy strand is 27.7% for A, 28.3% for T, 14.9% for G and 29.1% for C, with an A þ T bias of 59.9%, similar to other ranid species (Hofman et al 2014, Li et al 2014a, 2014b, Ni et al 2015. The genome shows a similar gene organization as other ranids (Kurabayashi et al 2010;Xia et al 2014), but it is the only anuran known so far lacking the tRNA Phe .…”
mentioning
confidence: 77%
“…This study included ten species that we sequenced ourselves and five species from GenBank; detailed information is shown in Table 1 and Fig 1. Within Table 1, The sequences with superscript numbers among the GenBank accession numbers are referenced as follows: 1, Zhou et al [17]; 2, Che et al [3]; 3; Zhou et al [18]; 4, Yan et al [11]; 5, Sumida et al [19]; 6, Lin et al [20]; 7, Ni et al [21]. This study was conducted in strict accordance with the recommendations in the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health.…”
Section: Methodsmentioning
confidence: 99%
“…catesbeiana and L . sylvatica ) from GenBank [20, 21] were selected as outgroups for phylogeny and divergent time analyses. P-distances were calculated using MEGA v.7.0.…”
Section: Methodsmentioning
confidence: 99%
“…Comparative analysis showed that the longest IGN between A. americanus and Bufotes pewzowi had a high similarity (76.9%). In many vertebrates, there is usually a trnL (CUN) gene following the trnS (AGY) gene (Cheng et al, 2018;Lin et al, 2014;Ni et al, 2016;Ye et al, 2016;. However, when the trnL (CUN) gene is translocated, an IGN is left in its original position (Zhou et al, 2009).…”
Section: Control Region and Intergenic Regionsmentioning
confidence: 99%